The wisdom books of the Bible Proverbs, Job, Ecclesiastes, Ben Sira, Wisdom of Solomon : a survey of the history of their interpretation - Kealy, Sean P. (Lewiston, N.Y. : Edwin Mellen Press, 2012)
"Where is the life we have lost in living? Where is the wisdom we have lost in knowledge? Where is knowledge we have lost in information?"
Title Page; Copyright Page; Table of Contents; Foreword; Introduction; Chapter 1: Proverbs; Chapter 2: Job; Chapter 3: Ecclesiastes (Qoheleth); Chapter 4: Ben Sira (Ecclesiasticus); Chapter 5: The Wisdom of Solomon; Chapter 6: Afterword; Index
Description based upon print version of record.
Keywords: Bible. O.T. Ecclesiastes -- Criticism, interpretation, etc. -- History -- 20th century; Bible. O.T. Proverbs -- Criticism, interpretation, etc. -- History -- 20th century; Wisdom literature -- Criticism, interpretation, etc. -- History; Religion; RELIGION / Biblical Studies / Old Testament; RELIGION / Biblical Studies / Wisdom Literature; Wisdom literature -- Criticism, interpretation, etc. -- History; Electronic books